2002
DOI: 10.1029/2001gl013991
|View full text |Cite
|
Sign up to set email alerts
|

Large density depletions in the nighttime upper ionosphere during the magnetic storm of July 15, 2000

Abstract: We measured electron density and temperature of the nighttime upper ionosphere for the several key intervals during the progress of the magnetic storm on 15 July 2000 with the Langmuir probe on Korea Multipurpose Satellite‐1 (KOMPSAT‐1). During the main phase of the storm KOMPSAT‐1 detected near 0°E a very deep and extensive trough of electron density centered around the geomagnetic equator. The electron density dropped sharply from ∼4 × 105cm−3 to less than 2 × 104cm−3, with the trough region extended over 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…In summarizing SIBB results Kil et al (2006) state [1] "They occur in the equatorial region at night, are elongated in the north-south direction, have steep walls, and always coexist with plasma bubbles." Satellite recordings by Lee et al (2002) have detected displacements of over 1400 km along a satellite path and a disturbance which extends at least 4500 km in the longitudinal direction. LS-TIDs have the same characteristics as SIBBs (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In summarizing SIBB results Kil et al (2006) state [1] "They occur in the equatorial region at night, are elongated in the north-south direction, have steep walls, and always coexist with plasma bubbles." Satellite recordings by Lee et al (2002) have detected displacements of over 1400 km along a satellite path and a disturbance which extends at least 4500 km in the longitudinal direction. LS-TIDs have the same characteristics as SIBBs (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Low-earth orbiting satellites have detected largescale ion density dropouts with a spatial width greater than 800 km in the low-latitude ionosphere during several magnetic superstorms (Greenspan et al, 1991;Basu et al, 2001;Lin et al, 2001, Lee et al, 2002Su et al, 2002;Lin and Yeh, 2005). Lin et al (2001) demonstrated that these large-scale density dropouts corotated with the South Atlantic anomaly (SAA) and were adjacent to regions of density enhancement, forming a magnetic anomaly density structure (MADS).…”
Section: Introductionmentioning
confidence: 98%
“…Sometimes the equatorial topside ionosphere can undergo a drastic depletion at 21:30 LT when a very intense magnetic storm occurs (e.g. Greenspan et al, 1991;Basu et al, 2001;Lee et al, 2002;Foster et al, 2002). Such situations are rarer during small and moderate magnetic storms.…”
Section: Further Analysismentioning
confidence: 99%